PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING (PBL) PADA TOPIK PROGRAM LINEAR UNTUK KELAS XI SMA - Egi Safitri (Departemen Matematika, 2021)
Thisstudy aims to develop a Student Worksheet (LKPD) on the topic of program linear for class XI high school students by applying Problem Based Learning. This type of research is development research using the Plomp which consists of three phase, namely preliminary research, prototyping, and the assessment. The preliminary research phase consist of needs analysis, curriculum, concept, and student analysis are carried out in order to obtain temporary characteristics of the developed LKPD. The development analysis phase, a prototype worksheet based on Problem Based Learning is made on program linear.After that, a formative evaluation was carried out on the LKPD prototype which was useful for improving and improving the developed prototype which consisted of self-evaluation, validation by expert review, evaluation one-to one, and small group evaluation to determine the validity and practicality of the LKPDResults of the validity it has met the very valid criteria with an average of 86.3% and has a practicality level of 88.2% with a very practical category, it can be concluded that the LKPD based on Problem Based Learning on the topic of program linear valid and practical. Keywords– LKPD, Problem Based Learning (PBL), Program Linear